Evaluation of the Relationship Between Patellar Position With Lower Limb Function and Balance in Athletes With Patellofemoral Pain Syndrome - Sara Asadi; Seyyed Hossein Hosseini; Hassan Daneshmandi (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Patellofemoral pain syndrome often results from misalignment of the patellofemoral joint that can affect lower limb function. Therefore, the present study investigated the relationship between patellar position and lower limb function and balance in athletes with patellofemoral pain syndrome. Methods In this exploratory analytical study, 39 male and female athletes with this syndrome with an average age of 25.6±4.7 years were selected by available sampling. Lower limb function and dynamic balance were measured by the Western Ontario and McMaster Universities Osteoarthritis index (WOMAC) scale and Y balance test, respectively, and patellar position was assessed by digital radiology. The Pearson correlation test was used to analyze the data at a significance level of 0.05. Results The results showed that the position of the patella was significantly associated with lower limb function and dynamic balance (P<0.01). Accordingly, lower limb function on the WOMAC scale had a significant positive relationship with patellar tilt angle and patellar congruence angle (P=0.001). Also, dynamic balance showed a significant negative relationship with patellar tilt angle (P=0.007) and patellar congruence angle (P=0.002). Conclusion According to the results of the present study, the higher the tilt angle and patellar homogeneity, the weaker, the lower limb function and dynamic balance. Therefore, it is suggested that the position of the patella should always be considered and corrected to improve performance and balance and promote the record of sports activities of athletes with this disorder and facilitate their return to sports.